PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN DI WARUNG CITA RASA CAK WANTO - Tina Cahya Sari; Meylani Tuti (Panorama Nusantara, 2017)
This study aims to determine the quality of products and prices affecting partially on customer satisfaction and to know the two variables that affect customer satisfaction. The data used in this study is the primary data obtained from the questionnaire. Data analysis used in this research is multiple linear regression. Population in this research is customer of small restaurant Cita Rasa Cak Wanto. The technique used is accidental sampling, with samples used 100 people. Then the validity test, reliability test, classical assumption test which includes normality test, multicolinearity, heteroscedasticity test, and linearity test. Whereas hypothesis testing includes F test, t test and determination coefficient analysis (R2) from the analysis can be known product quality and price partially and simultaneously have an effect on to customer satisfaction.